Symposium 3: The Influence of Chinese Culture on Trainees’ Online Behaviours in a Teacher Training Course - Chen, Zehang (Proceedings of the International Conference on Networked Learning, 2006)
This paper explores Chinese learners’ online behaviours in a teacher training course which was developed as part of a Chinese and UK government funded collaborative project from 2003 to 2005 by the University of Nottingham, UK and Beijing Normal University, China. The aim of the project is to develop innovative eLearning materials for Chinese teachers of English. The paper focuses on the influence of Chinese culture on learners behaviors, leading to the conclusion that culture influence is an important issue that should be taken into consideration by online course developers.